A Critical Review of Analytical Methods for Quantification of Cefotaxime - Consortti, Livia Paganini [UNESP]; Nunes Salgado, Herida Regina [UNESP] (Taylor & Francis Inc, 2017)
Bacterial resistance to antibiotics is a growing phenomenon in the world. Considering the relevance of antimicrobials for population and the reduction in the registration of new antimicrobials by regulatory, proper quality control is required in order to minimize the spread of bacterial resistance and ensure the effectiveness of a treatment, as well as safety for the patient. Among the antimicrobials is cefotaxime, a drug belonging to third-generation cephalosporins, which is highly active against Gram-negative bacteria and is used to treat central nervous system infections such as meningitis and septicemia. Due to the critical importance of quality control in regard to drugs and pharmaceutical products, combined with bacterial resistance to antibiotics, this study aims to conduct a detailed review of analytical methods for cefotaxime. Using a critical review of literature, this paper describes the analytical methods published to quantify cefotaxime in different matrices; a large number of methods by HPLC and spectrophotometry were observed. Despite the advantages of the techniques, most methods reported have large environment and occupational impact, which enfatizes the need to adopt green procedures in quantifying cefotaxime.
Keywords: Analytical methods; cefotaxime; HPLC; quality control; review